Suboptimal diabetic control and psychological burden after the triple disaster in Japan: the Fukushima Health Management Survey. Issue 1 (8th September 2021) - Hirai, Hiroyuki; Okazaki, Kanako; Ohira, Tetsuya; Maeda, Masaharu; Sakai, Akira; Nakano, Hironori; Hayashi, Fumikazu; Nagao, Masanori; Harigane, Mayumi; Takahashi, Atsushi; Ohira, Hiromasa; Kazama, Junichiro James; et al.
Abstract : Introduction: A triple disaster struck eastern Japan in March 2011. We investigated the psychological distress and post-traumatic stress disorder (PTSD) symptoms caused by the disaster in people without or with diabetes mellitus. Research design and methods: This cross-sectional analysis examined the 16 097 evacuees (1820 (11.3%) with and 14 277 (88.7%) without diabetes mellitus) included in the Fukushima Health Management Survey. Non-specific mental health distress was assessed using the Kessler-6 Scale, and traumatic symptoms were evaluated using the PTSD Checklist. Logistic regression analyses were used to estimate the OR and 95% CI associated with symptoms, adjusted for diabetes-related and disaster-related factors. Results: In the age-adjusted and sex-adjusted logistic models, suboptimal diabetic control (hemoglobin A1c (HbA1c) ≥7%) was associated with both psychological distress and possible PTSD. In the same models, current smoking, evacuation, and sleep dissatisfaction were associated with psychological distress and possible PTSD. In the multivariate-adjusted logistic models, HbA1c ≥7% was associated with psychological distress, independent of job change, evacuation, or sleep dissatisfaction. Conclusion: After the triple disaster, non-specific mental health distress was associated with suboptimal diabetic control. Thus, patients with diabetes, especially those with suboptimal diabetic control, may be vulnerable to postdisaster psychological burden.